(untitled) (Scottish Historical and Archaeological Internet Reports, 2010)
This chapter is concerned with the boundaries of Dalkeith Park formerly the formal gardens and grounds of the 18th-century Dalkeith House. Survey methodology and results are considered. Within the sections of wall examined by evaluation it was clear that there was uniformity in its design.